Tyrosol prevents AlCl3 induced male reproductive damage by suppressing apoptosis and activating the Nrf-2/HO-1 pathway - Guvenc, Mehmet; Cellat, Mustafa; Gokcek, Ishak; Arkali, Gozde; Uyar, Ahmet; Tekeli, Ibrahim Ozan; Yavas, Ilker (Wiley, 2020)
Aluminium is a ubiquitous element that occurs naturally in the soil making human exposure to it is unavoidable. Tyrosol is present in olive oil and is known to have antioxidant effects. Therefore, the present study explores the toxic effects of aluminium chloride (AlCl3) and evaluates the possible protection by tyrosol in male rats. Testicular injury was induced by the administration of AlCl3 (34 mg kg(-1) day(-1)). Rats were treated with either tyrosol (20 mg kg(-1) day(-1)) or AlCl3 (34 mg kg(-1) day(-1)). The experiment lasted for 10 weeks. Biochemical, histopathological and protein expression profiles were determined to decipher the role of tyrosol in protecting the cellular damage. Further, histomorphometric analyses of testes showed deranged architecture along with other noted abnormalities. AlCl3 group rats' testes showed decreased GSH levels, CAT activities, Nrf-2, HO-1, bcl-2 expressions and sperm motility whereas increased caspase-3 expressions, MDA levels, abnormal and dead/live sperm ratio. However, tyrosol treatment attenuated these changes. The present results demonstrate the beneficial role of tyrosol treatment in AlCl3 induced testicular toxicity alterations of rat.
Keywords: aluminium chloride; antioxidant; apoptosis and sperm quality; tyrosol